Successful Implementation of Enterprise Resource Planning - Hermawan Hermawan (The Winners, 2019)
The purpose of this research was to analyze factors that influence a successful implementation of Enterprise Resource Planning (ERP) at PT Agung Sedayu Group. Measuring the success of ERP implementation was needed to find out what success factors influence the implementation process. The DeLone and McLean success model was used as a measurement tool with employees who actively used the ERP system as respondents. The research method used was a descriptive quantitative method with questionnaires as data collection techniques with the indicators on DeLone and McLean model. Data taken from the questionnaire were 187 samples from 350 active user population systems at PT Agung Sedayu Group. Questionnaire data were processed using the SPSS application to test the validity and reliability; then linear regression analysis was performed to test the hypothesis. From the results of the research, it is known that all variables of system quality, information quality, service quality, usage, user satisfaction, and net benefits have an influence on the successful implementation of ERP at PT Agung Sedayu Group. The conclusion presents that the successful implementation of ERP is more influenced by user satisfaction supported by the level of use, system quality, information quality, and service quality.